AFORISME AL-QURAN DAN HERMENEUTIKA TERBUKA IBN Aá¹¬Ã‚â€™ ALLAH ATAS AYAT-AYAT KEHENDAK - Syaifullah, Muhammad (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2018)
This essay tries to explicate how Ibn â€˜Aá¹Ã¢â€˜ Allah understands Qurâ€™an within his popular book, al-á¸¤ikÃ¢m. It is not merely his huge opus yet one of several books in which Indonesian Moslems like to learn and discuss. It covers the opened aphorisms stands on three entities, these are Qurâ€™an, hadith, including some habits of Prophet Muhammad and subsequently I opt al-á¸¤ikÃ¢m. As a sample, I am such demanded to come in through his interpretation concerning â€œwillâ€ or kehendak. Ibn â€˜Aá¹Ã¢â€˜ Allah, as far as I feel, has deep conception with regard to â€œwillâ€ which is wallowed with dilemma. Sometime, he puts it as something freely owned by human, sometime on the contrary. By that conception, Ibn â€˜Aá¹Ã¢â€˜ Allah covets an ideal figure such â€œsupermanâ€â€”to borrow Nietzsche phraseâ€”as if. A super human that prefer living within dark surrounding to comfort, that is able to reflect his hard problems often and then solve it well. This article thus interests to look further how Ibn â€˜Aá¹Ã¢â€˜ Allahâ€™s hermeneutic model, particularly when composing al-á¸¤ikÃ¢m. Who is his target audiences and how does it absorb to daily activities. The essay argues that Ibn â€˜Aá¹Ã¢â€˜ Allahâ€™s prescription in approaching Qurâ€™an is going to a couple point, these are what I call as â€œcreative abstractionâ€ and an endeavor to reinvent Quranic mode or â€œreinvention of Quranic modeâ€.Keywords: Ibn â€˜Aá¹Ã¢â€˜ Allah, the opened hermeneutic, creative abstraction.